2022
DOI: 10.1007/s10935-022-00719-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing COVID-19 Prevention Behaviors

Abstract: COVID-19 remains a public health emergency with prevention guidelines and mitigation strategies being constantly updated to curb the rapid spread of the disease. Despite proven successes of recommended preventive behaviors, there is low uptake of wearing a mask, washing of hands, and social distancing in the United States (US). The purpose of this study was to examine factors that influence COVID-19 preventive behaviors. We used data from the nationally representative COVID-19 Household Impact Survey (n = 19,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This postulates a crucial influence of personal motivation and close social networks, as only 16% reported using home remedy based on the recommendations from other individuals. A study investigating factors influencing COVID-19 preventive behaviour found that individuals can be socially influenced when trusted individuals in their social circle adhere to a social norm [ 37 ]. A global systematic review highlighted that people primarily turn to CAM due to their expectations of its benefits, discontentment with conventional medicine, and the perceived safety of CAM [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This postulates a crucial influence of personal motivation and close social networks, as only 16% reported using home remedy based on the recommendations from other individuals. A study investigating factors influencing COVID-19 preventive behaviour found that individuals can be socially influenced when trusted individuals in their social circle adhere to a social norm [ 37 ]. A global systematic review highlighted that people primarily turn to CAM due to their expectations of its benefits, discontentment with conventional medicine, and the perceived safety of CAM [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Age is a significant factor that correlates with COVID-19 prevention behavior (8,10,20). Elderly individuals have a weakened immune system compared to adolescent and adult individuals, especially if they have comorbidities (21).…”
Section: Discussionmentioning
confidence: 99%
“…One important aspect of community behavior is compliance with public health guedilines, such as using masks, hand washing, bring hand sanitizer, and social distancing. This series of health protection behaviors has been proposed by World Health Organization (WHO) to become a global plan to prevent the spread of covid-19 infection (8). In Indonesia, the government has made various efforts to prevent and reduce the prevalence and mortality due to covid-19 virus infection, such as implementing the health protocol, namely 3M, which includes wearing masks, washing hands and maintaining distance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disparities in COVID-19 vaccination, as well as other COVID-19 prevention behaviors, exist between high- and lower-income individuals and communities in the United States. ( Brownstein et al, 2022 , Cheng and Li, 2022 , Wachira et al, 2022 ) Racial-ethnic disparities in vaccine willingness and uptake have also been observed. ( Pingali et al, 2021 , Nápoles et al, 2021 ) However, less is known about how income disparities and racial-ethnic disparities in COVID-19 vaccine willingness and uptake intersect.…”
Section: Introductionmentioning
confidence: 99%